2021
DOI: 10.3389/fpsyt.2020.609819
|View full text |Cite
|
Sign up to set email alerts
|

Rehabilitation and Disability Spectrum From Adverse Childhood Experience: The Impact of the Movement Cognition and Narration of Emotions Treatment (MCNT) Version 2.0

Abstract: Adverse Childhood Experiences (ACE) are associated with an increased risk of cerebral, behavioral, and cognitive outcomes, and vulnerability to develop a Borderline Intellectual Functioning (BIF). BIF is characterized by an intelligence quotient (IQ) in the range 70–85, poor executive functioning, difficulties in emotion processing, and motor competencies. All these difficulties can lead to mental and/or neurodevelopmental disorders that require long-term care. Accordingly, we developed an intensive and multid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 59 publications
(41 reference statements)
0
2
0
Order By: Relevance
“…Specifically, we used a multimodal approach named movement cognitive and narration of the emotions treatment (MCNT), in which the relational dimension was the core of the treatment. Results of our studies showed that despite the positive and motivating properties of the technology involved, the relational dimension was decisive in promoting significant results in all three domains in this population (Baglio et al, 2020;Blasi et al, 2020b).…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…Specifically, we used a multimodal approach named movement cognitive and narration of the emotions treatment (MCNT), in which the relational dimension was the core of the treatment. Results of our studies showed that despite the positive and motivating properties of the technology involved, the relational dimension was decisive in promoting significant results in all three domains in this population (Baglio et al, 2020;Blasi et al, 2020b).…”
Section: Discussionmentioning
confidence: 66%
“…Finally, the need for a user-centered and personalized design to ensure that the needs and specificities of patients are more effectively met is well-recognized (Parsons et al, 2017;Halldorsson et al, 2021;Karami et al, 2021). Accordingly, previous works (Baglio et al, 2020;Blasi et al, 2020b) investigated the effects of different rehabilitation programs for children with BIF, comparing interventions with and without the use of new technologies. Results highlighted how a game-therapy approach that applied highly engaging and motivating technological devices (Wii and Xbox) was not effective in promoting motor planning abilities in children with BIF, but, the use of a body-awareness approach which involved learning body management techniques, thanks to the relationship with the therapist, proved to be effective.…”
Section: Introductionmentioning
confidence: 99%